Application of Authentic Assessment in The 2013 Curriculum on Thematic Learning Themes “ Daerah Tempat Tinggalku “ - Ulil Maziyatin Nafisyah; Sofyan Hadi; Lailatul Usriyah (EDUTEC : Journal of Education And Technology, 2023)
The purpose of the study was to describe the authentic assessment of attitude, knowledge and skills competencies in thematic learning at MI Nurul Islam 02 Balung Jember. This research uses a qualitative research approach and case study research type. The location of this research is MI Nurul Islam 02 Balung Jember. Determination of informants using purposive technique. Data collection techniques using non-participant observation, semi-structured interviews. Data analysis using data condensation, data presentation, drawing conclusions or verification. The results of this study are 1) Authentic assessment of attitude competence in thematic learning at MI Nurul Islam 02 Balung Jember includes spiritual attitudes and social attitudes 2) Authentic assessment of knowledge competence is using written tests, oral tests and assignments. On the theme of 8 Regions Where I Live sub-theme 1 learning to 1 knowledge assessment is carried out in written tests and assignments, written tests are making sentences from a word, and pairing buildings and nets of building spaces. The assignment is that the teacher gives homework in groups. 3) Authentic assessment of skill competencies in thematic learning in the form of portfolio, project, and performance assessments. Skills assessment is seen from students' skills when doing storytelling activities.